Incidence and mortality of cervical cancer in French Guiana: Temporal and spatial trends - Laure Manuella Imounga; Juliette Plenet; Sophie Belliardo; Elie Chow Chine; Antoine Adenis; Mélanie Gaillet; Nadia Thomas; Céline Michaud; Véronique Servas; Pierre Couppié; Kinan Drak Alsibai; Mathieu Nacher (Elsevier, 2021)
Objectives: Cervical cancer is the second most frequent cancer among women in French Guiana. The objective was to review a decade of cervical cancer data, and to study spatial and temporal trends. Study design: The design was retrospective and descriptive. Methods: The cancer registry of French Guiana compiled exhaustive data on cervical cancer throughout French Guiana between 2005 and 2015. Age-standardized incidence and mortality were computed and mapped to identify priority areas. Results: With 232 new cases recorded in French Guiana between 2005 and 2014 (23 annual cases), cervical cancer ranked 5th among all incident cancers (11%) and was the 2nd most frequent cancer in women (12% of cancers among women). The standardized incidence rate over the period 2005-2014 was 23.8 cases of cervical cancer per 100 000 woman-years. Between 2005-2009 and 2010-2014 the incidence of cervical cancer decreased from 26.26 cases per 100 000 to 22.66 cases per 100 000 and the mortality rate from cervical cancer decreased from 6 deaths per 100 000 to 3.2 deaths per 100 000.Within French Guiana, the standardized incidence rates were very heterogenous with the highest rates in remote areas. The standardized death rate from cervical cancer over the 2005-2014 decade was 4.4 cases per 100 000 woman-years. Conclusions: The present results suggest there has been progress in French Guiana, but there are still areas where screening is challenging and should be expanded. The recent authorization of HPV testing is an opportunity that could help health professionals achieve this goal. HPV vaccination -with a nonavalent vaccine-is also an important public health endeavor that could alleviate the burden of cervical cancer among the cohorts of women benefitting from it.